2020
DOI: 10.1093/gbe/evaa187
|View full text |Cite
|
Sign up to set email alerts
|

Improved Reference Genome Uncovers Novel Sex-Linked Regions in the Guppy (Poecilia reticulata)

Abstract: Theory predicts that the sexes can achieve greater fitness if loci with sexually antagonistic polymorphisms become linked to the sex determining loci, and this can favour the spread of reduced recombination around sex determining regions. Given that sex-linked regions are frequently repetitive and highly heterozygous, few complete Y chromosome assemblies are available to test these ideas. The guppy system (Poecilia reticulata) has long been invoked as an example of sex chromosome formation resulting from sexua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
109
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(122 citation statements)
references
References 90 publications
(137 reference statements)
12
109
1
Order By: Relevance
“…Selection scans may overlook some of our association outlier windows because differentiation at these loci may be moderate, but rather we are detecting consistent allele frequency changes in the same direction between HP-LP comparisons. Many of the associated windows mapped to a previously unplaced scaffold in the genome (000094F), but we were able to place this at the start of chromosome 20 along with some local rearrangements (Figure S6) using previously published HiC data [61]. From here on and in Figure 2C-D, we refer to this new arrangement for chromosome 20 and scaffold 000094F as chromosome 20.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…Selection scans may overlook some of our association outlier windows because differentiation at these loci may be moderate, but rather we are detecting consistent allele frequency changes in the same direction between HP-LP comparisons. Many of the associated windows mapped to a previously unplaced scaffold in the genome (000094F), but we were able to place this at the start of chromosome 20 along with some local rearrangements (Figure S6) using previously published HiC data [61]. From here on and in Figure 2C-D, we refer to this new arrangement for chromosome 20 and scaffold 000094F as chromosome 20.…”
Section: Resultsmentioning
confidence: 79%
“…LITE libraries were sequenced on an Illumina HiSeq4000 with a 150bp paired-end metric and a target insert size of 300bp, and were pooled across several lanes so as to avoid technical bias with a sequencing coverage target of ≥10x per sample. Data from the Guanapo and Oropouche rivers has been previously published as part of Fraser et al [61].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, a comparative study showed that in Neurospora tetrasperma large inversions present in the mat chromosome are a consequence instead of a cause of suppressed recombination ( Sun et al 2017 ; and see additional examples in Vicoso et al 2013 and Yan et al 2020 ). Likewise, population-level studies of young supergenes ( table 1 ) can contribute to a more refined characterization of the early stages of supergene evolution, as has been the case for young sex chromosomes (for instance, in guppies: Bergero et al 2019 ; Fraser et al 2020 , see also reviews by Charlesworth 2019 and Furman et al 2020 ).…”
Section: Molecular Mechanisms Of Recombination Suppression At Supergenesmentioning
confidence: 99%